PENGARUH MEDIA VIDEO PEMBELAJARAN TERHADAP MOTIVASI DAN PEMAHAMAN AHLAK SISWA DALAM MENGIMPLEMENTASIKAN KEHIDUPAN SEHARI-HARI DI UPTD SDN KAMPAK 4 GEGGER BANGKALAN - Moh.Rosek; Pratiwi, Siska (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The results of the implementation of PLP II that I experienced at UPTD SDN KAMPAK 4 GEGER BANGKALAN, learning so far has not reflected motivation and understanding in students because there are still students who play alone and lack focus in listening to the material when the teacher explains it and there are also those who talk to their classmates. The aim of this research is to determine the effect of learning video media on students' motivation and understanding of morals in implementing daily life at UPTD SDN Kampak 4 Gegger Bangkalan. The number of subjects in this study was 34 grade 6 students at UPTD SDN Kampak 4. The instrument used in this research is a non-test instrument (questionnaire). The research method used was quantitative with an experimental design type one group pretest-posttest design. The data analysis techniques used in this research are Validity Test, Reliability Test, Normality Test, Paired Sample T Test, and Manova Test. With the results of the Manova test analysis, it was obtained that the data description had a significance result of 0.000 <0.05, so the independent variable (learning video media) had a significant effect on the dependent variable (motivation and understanding of students' morals). So it can be concluded, there is an influence of learning video media on students' motivation and understanding of morals in implementing daily life at UPTD SDN Kampak 4 Gegger Bangkalan.